The Algorithmic Self: Rethinking Consciousness And Personal Identity In The Era Of Brain-Computer Interfaces - Arief Budi Pratomo; Rustiyana Rustiyana (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid integration of Brain-Computer Interfaces (BCIs) into human cognitive processes has initiated a profound transformation in how consciousness and personal identity are conceptualized. As neural data become digitized, the boundaries between human cognition and machine computation blur, leading to the emergence of what can be described as the algorithmic self a hybrid consciousness co-produced by biological and artificial systems. Purpose. This research aims to examine how BCIs reshape the phenomenology of selfhood, agency, and memory by mediating the interaction between neural intention and algorithmic feedback. Method. The study employs a qualitative phenomenological design complemented by neuroscientific literature analysis, focusing on participants using non-invasive BCIs for communication, learning, and rehabilitation. Data were collected through in-depth interviews, reflective diaries, and neuro-ethical discourse mapping to identify cognitive and existential shifts in participants’ self-perception. Results. The findings reveal that BCI users experience fragmented yet extended forms of consciousness, where identity is continuously negotiated between embodied experience and algorithmic prediction. Participants reported increased cognitive augmentation but also existential dissonance, expressing uncertainty over the locus of agency and authorship of thought. Conclusion. The study concludes that the algorithmic self represents a new stage in human consciousness an emergent, co-dependent identity formed through neural–digital symbiosis. These findings call for an interdisciplinary rethinking of personhood, ethics, and autonomy in the age of neurotechnology.